2021
DOI: 10.1002/pol.20210554
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic double network hydrogels: Combining dynamic and static crosslinks to enable biofabrication and control cell‐matrix interactions

Abstract: Hydrogels are promising candidates for recapitulation of the native extracellular matrix (ECM), yet recreating molecular and spatiotemporal complexity within a single network remains a challenge. Double network (DN) hydrogels are a promising step towards recapitulating the multicomponent ECM and have enhanced mechanical properties. Here, we investigate DNs based on dynamic covalent and covalent bonds to mimic the dynamicity of the ECM and enable biofabrication. We also investigate the spatiotemporal molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…While we and others have developed orally administrable tough hydrogels 55, 58, 59 , these require templated radical polymerization of toxic acrylamide monomer that cannot be safely performed in vivo and are dosed as a solid 60 . Other hydrogel systems have been designed that require UV light to facilitate polymer crosslinking 61, 62 , utilize polyacrylamide as a polymer network 37 , require a specific construction of hydrogel components 59 , or are enzymatically polymerized 63, 64 . While these hydrogels are mechanically tough, they either require a pre-solidified dosage format or are challenging and unsafe to crosslink and gel in situ .…”
Section: Discussionmentioning
confidence: 99%
“…While we and others have developed orally administrable tough hydrogels 55, 58, 59 , these require templated radical polymerization of toxic acrylamide monomer that cannot be safely performed in vivo and are dosed as a solid 60 . Other hydrogel systems have been designed that require UV light to facilitate polymer crosslinking 61, 62 , utilize polyacrylamide as a polymer network 37 , require a specific construction of hydrogel components 59 , or are enzymatically polymerized 63, 64 . While these hydrogels are mechanically tough, they either require a pre-solidified dosage format or are challenging and unsafe to crosslink and gel in situ .…”
Section: Discussionmentioning
confidence: 99%
“…68,69 A growing number of studies have shown that the use of both dynamic covalent and non-covalent interactions to form hybrid crosslinked hydrogels overcomes important limitations of purely dynamic covalent or noncovalent hydrogels. [70][71][72] For example, single hydrogen bonds between hydroxyl, carboxyl and amino groups are not strong enough to form hydrogels by themselves, and hydrophobically crosslinked hydrogels generally exhibit poor mechanical strength. Moreover, Schiff base bonds are mechanically weak and highly sensitive to hydrolysis with pH shifts.…”
Section: Crosslinking Strategiesmentioning
confidence: 99%
“…For example, oxidized Alg (OA) was used to form a dynamic first network by Schiff-base reaction, while the polyethylene glycol diacrylate (PEGDA) acted as the second covalent network (Figure 6B). 90 The synergetic effect of both networks provides the hydrogel with self-healing ability and injectability as well as excellent stability. Similarly, Chen et al 91 prepared dopamine (DA)-grafted OA to interact with PAAm chains via Schiff cross-linking.…”
Section: Alginate-based Dn Hydrogelsmentioning
confidence: 99%
“…Reproduced with permission. 90 Copyright Wiley 2021 engineering, and strain sensors. 103 The DN hydrogel based on poly (acrylic acid-co-acrylamide) (PAA-co-PAAm) and HA showed an excellent sensory to strain, temperature, and humidity.…”
Section: Hyaluronic Acid-based Dn Hydrogelsmentioning
confidence: 99%